Kepuasan Kerja Perawat pada Rumah Sakit Wava Husada dilihat dari Beban Kerja, Lingkungan Kerja dan Motivasi Kerja - Nurkumalasari, Siti; Sinollah; RR. Hesti Setyodyah Lestari (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2024)
This study aims to find out and analyze the influence of workload, work environment, and work motivation on nurses' job satisfaction at Wava Husada Hospital. To achieve this goal, this research uses quantitative methods using multiple linear regression analysis. The results of this study show that workload partially has a significant effect on the job satisfaction of Wava Husada Hospital nurses, the work environment partially has a significant effect on the work satisfaction of Wava Husada Hospital nurses, work motivation partially has a significant effect on the job satisfaction of Wava Husada Hospital nurses. Workload, work environment, and work motivation simultaneously have a significant effect on the job satisfaction of nurses at Wava Husada Hospital. For this reason, the management of Wava Husada Hospital can still balance the workload of nurses with their abilities and maintain the work environment and work motivation of its nurses